2020
DOI: 10.1002/icd.2211
|View full text |Cite
|
Sign up to set email alerts
|

Predicting early reading fluency based on preschool measures of low‐level visual temporal processing: A possible mediation by high‐level visual temporal processing skills

Abstract: Fluent reading, which involves visual serial processing of letters/characters (i.e., visual temporal processing, VTP), greatly contributes to our daily life. The present study thus explored the underlying mechanism of reading fluency from the perspective of VTP. A longitudinal method was adopted to examine whether VTP skills in preschool (mean age of 5.03 ± 0.06 years) could predict reading fluency after 2 years (mean age of 7.10 ± 0.18 years). Low‐ and high‐level VTP skills were systematically measured. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…Regarding time perception, prior research has shown that visual and auditory temporal processing abilities in preschool predicted letter and word recognition as well as reading fluency in primary school (Hood & Conlon, 2004;Liu et al, 2020). Moreover, preschoolers at risk of developing dyscalculia were observed to perform more poorly in timing tasks compared to their typically developing peers (Tobia et al, 2016), implying a correlation between dyscalculia and timing ability.…”
Section: Neuropsychological Models Of Adhdmentioning
confidence: 97%
“…Regarding time perception, prior research has shown that visual and auditory temporal processing abilities in preschool predicted letter and word recognition as well as reading fluency in primary school (Hood & Conlon, 2004;Liu et al, 2020). Moreover, preschoolers at risk of developing dyscalculia were observed to perform more poorly in timing tasks compared to their typically developing peers (Tobia et al, 2016), implying a correlation between dyscalculia and timing ability.…”
Section: Neuropsychological Models Of Adhdmentioning
confidence: 97%